Optimization Of Bushing Production Time In Cnc Turning Process Using Taguchi and Root Cause Analysis (Rca) Method - Achmad Yani; Wiwik Sulistyowati (Universitas Muhammadiyah Sidoarjo, 2021)
PT. WT is a company engaged in the manufacturing industry. To support the fulfillment of the above production results, this company already has several units of sophisticated CNC machines. However, in the application of this CNC machine, there are still problems when making bushing spare parts that have not been able to meet the very high market demand.This is because within 16 hours of effective work it only produces 120 pcs of bushing spare parts, while in 1 month the demand for bushing spare parts from consumers reaches 2,400 pcs. So that in this study, it is necessary to improve the time and quality of production which is more effective and efficient.The research that has been done with the title